Validation of self-regulated learning instrument on pre-clinical medical students at University of Malaya - Vadivelu, Jamuna (2017)
Many medical schools are adopting strategies and pedagogies to help students develop a self-regulated learning ability which is a key aspect of lifelong learning. Self regulation is defined as "self-generated thoughts, feelings, and actions that are planned and cyclically adapted to the attainment of personal goals" (Zimmerman, 2000). This will enable the students to take responsibility for, direct and regulate their own learning to achieve their learning goals (Chen & Schwartz, 2014). The three important characteristics of self-regulated learners are goal-directed behavior, use of specific strategies to attain goals, and the adaptation and modification to one's behaviours or strategies to optimize learning (Sandars & Cleary, 2011). This involves iterative cycles of forethought, performance and self-reflection (Chen & Schwartz, 2014).